1987
DOI: 10.3727/015613887791918150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Chicks on Maternal Behaviour in Domestic Chickens

Abstract: International audienceTwo different procedures were followed to induce maternal behaviour in domestic hens. When chicks were placed under hens during the night, the majority of adults presented maternal behaviour the following morning. When chicks were placed in cages at the beginning of the photophase, maternal responses appeared after a 24 h delay; hens first avoided or were aggressive towards chicks. The results are discussed in terms of hens becoming familiar with auditory, tactile and visual stimuli from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Research investigating the factors underlying this decline in maternal care has mostly focused on changes in the sensory cues from the continuously developing offspring and concludes that cues from older pups are unable to evoke strong maternal responses from the mothers. In support, early research on laboratory rats showed that the decline in mothering across lactation could be prevented if older litters are replaced with younger litters (Reisbick et al, 1975; Rosenblatt, 1969), and a similar phenomenon has been reported for brooding behavior in hens (Richard-Yris and Leboucher, 1987). This is partly due to the fact that younger pups are especially rewarding to mother rats (Wansaw et al, 2008), and even maternally inexperienced nulliparous rats are more likely to approach and act maternally to younger pups than older pups (Stern and Mackinnon, 1978).…”
Section: Introductionmentioning
confidence: 59%
“…Research investigating the factors underlying this decline in maternal care has mostly focused on changes in the sensory cues from the continuously developing offspring and concludes that cues from older pups are unable to evoke strong maternal responses from the mothers. In support, early research on laboratory rats showed that the decline in mothering across lactation could be prevented if older litters are replaced with younger litters (Reisbick et al, 1975; Rosenblatt, 1969), and a similar phenomenon has been reported for brooding behavior in hens (Richard-Yris and Leboucher, 1987). This is partly due to the fact that younger pups are especially rewarding to mother rats (Wansaw et al, 2008), and even maternally inexperienced nulliparous rats are more likely to approach and act maternally to younger pups than older pups (Stern and Mackinnon, 1978).…”
Section: Introductionmentioning
confidence: 59%
“…Similar phenomena have long been reported in vertebrates ( van Iersel 1953; Noirot & Richards 1966; Poindron et al . 1980 ; Richard‐Yris & Leboucher 1987). This has also been documented in some insect species ( Vancassel et al .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that HSR females emitted fewer cooing calls after reunion with their chicks compared to LSR females. These cooing calls have been reported to calm the chicks after the stress induced by separation of the mother and are a good indicator of a strong mother‐young attachment in hens. Therefore, the decreased vocal response observed in HSR females could indicate a loser bond with their chicks compared to LSR mothers.…”
Section: Discussionmentioning
confidence: 94%
“…These cooing calls have been reported to calm the chicks after the stress induced by separation of the mother 43 and are a good indicator of a strong mother-young attachment in hens 28 . Therefore, the In addition, both HSR and LSR females showed little aggression towards chicks.…”
Section: Maternal Behaviour In Lsr and Hsr Femalesmentioning
confidence: 91%
See 1 more Smart Citation